Effect of Information and Communication Technologies on Academic Achievement of High School Students in Neyriz - Eslamian, Davod; Khademi, Behbood (American Journal of Humanities and Social Sciences, 2017)
The objective of this study is to determine the effects of information and communication technology (ICT) on high school student academic achievement. The main hypothesis is postulated and tested in the study is: ICTs has no statistically significant effect on students’ achievement. The research is conducted in public high schools in the city of Neyriz, Iran in 2016. A total of 346 participants were employed for the study. The self-administrated survey questionnaire based on 5-point Likert scale was used to collect the data. The data were analyzed using descriptive and inferential statistics. The results of this study show that information technology communication has a significant effect on student achievement. The results are expected to highlight significant effects of ICT on students’ academic performance and issues related to further improvement in teacher education programs.